Prognostic value of angiopoietin-2 in patients with chronic heart failure. (1st June 2016) - Eleuteri, Ermanno; Di Stefano, Antonino; Giordano, Andrea; Corrà, Ugo; Tarro Genta, Franco; Gnemmi, Isabella; Giannuzzi, Pantaleo
Abstract: Purpose: The analysis of biomarkers with a prognostic value in chronic heart failure (CHF) is in constant progress. This study aimed to evaluate the short-term prognostic value of angiopoietin-2 (Ang2), galectin-3 (Gal-3), myeloperoxidase (MPO), endostatin (End), and pro-brain natriuretic peptide (pro-BNP) as a conventionally accepted prognosis biomarker in CHF patients. Methods and results: 146 consecutive patients with CHF due to left ventricular systolic dysfunction (LVEF < 40% at echocardiography) were enrolled, and underwent serum/blood sample analysis after 12-h fasting. Within 1 year, 25 (17%) patients died (D) or underwent heart transplantation (HT). D + HT patients showed higher values of Ang2 (Log Ang2: 8.97 ± 0.52 vs. 8.45 ± 0.69, p = 0.0004), myeloperoxidase (MPO) (Log MPO: 5 ± 1.1 vs. 4.2 ± 1.3, p = 0.005) and pro-BNP (Log pro-BNP: 8.70 ± 0.9 vs. 7.45 ± 1.3, p < 0.00001). At univariate Cox regression, pro-BNP and Ang2 were the best predictors of 1-year mortality, with area under the curve (AUC) = 0.78 for pro-BNP (68% sensitivity and 82% specificity to predict outcome for a cut-off value of 5109 pg/mL, 95% confidence interval [CI] 0.70–0.85, p < 0.0001) and AUC = 0.73 for Ang2 (84% sensitivity and 61% specificity to predict outcome for a cut-off value of 5175 pg/mL, 95% CI 0.65–0.80, p < 0.0001). At multivariate analysis, pro-BNP was the only predictor of one-year D/HT. Conclusion: In our series of CHF patients, Ang2 and pro-BNP showed the best predictive value for 1-year outcome, while only pro-BNP could independently predict D/HT.